ROTATION OF THE FIRST UPPER MOLARS - Papazyan, A.T. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The aim of the research is studying of morbidity of relation of the first upper molars, its influence on appearance and development of maxillodental anomalies. There were held researches among 170 pairs of upper and lower dental arch’s casts in orthodontic patients aged from 8 to 22 with different anomalies of teeth position, dental arches, occlusion. With the aim of studying of the first molars position there were scanned casts and their graphical digital pictures in two-level flat were got. The investigations showed that from the 340 upper first molars 31 had a correct orientation. So, the analysis of the held investigations point out the fact, that first upper molars mesial rotation is spread among orthodontic patients with different types of maxillodental anomalies in 91% cases. Taking it into account, in our opinion, it is important to include the special elements in orthodontic applianse’s construction which role consists in the derotation of molars.